A looming mental health pandemic in the time of COVID-19? Role of fortitude in the interrelationship between loneliness, anxiety, and life satisfaction among young adults. (June 2021) - Pretorius, Tyrone; Padmanabhanunni, Anita
This study investigates loneliness, anxiety, and life satisfaction among a sample of young adults in South Africa during the COVID-19 pandemic, as well as the role of fortitude in the interrelationship between these variables. Fortitude refers to the psychological strength to manage stress and stay well, and it is derived from positive appraisals of self, family, and support from others. Participants included 337 young adults who completed four self-report questionnaires: the UCLA Loneliness Scale, the State-Trait Anxiety Scale, the Satisfaction with Life scale, and the Fortitude Questionnaire. Stepwise regression analysis was performed to determine the direct, indirect, mediating, and moderating role of fortitude on psychological outcomes. The results demonstrated unprecedented levels of anxiety, loneliness, and reduced life satisfaction among the sample. These levels were significantly higher than those encountered in previous studies in other contexts, as well as in studies of similar populations conducted during the COVID-19 pandemic. Women reported higher levels of psychological distress than men. The results confirmed the mediating role of fortitude; however, they also suggested that the predictors (loneliness and anxiety) are the mediated pathways and fortitude is causally antecedent to loneliness and anxiety. These findings suggest a looming mental health crisis among young adults in South Africa and identify potential targets for intervention efforts. A strengths-based approach that focuses on enhancing individuals' appraisals of coping and support may serve to build fortitude and potentially mitigate adverse mental health outcomes.